Good Corporate Governance Dan Budaya Organisasi Meminimalisasi Kecenderungan Kecurangan Akuntansi Di Lembaga Perkreditan Desa - Latrini, Made Yenni; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
This research aims to determine the influence of Good Corporate Governance (GCG) and organizational culture on the tendency of accounting fraud in the Tabanan Regency Village Credit Institution (LPD). This research was conducted in all LPDs in Tabanan Regency. The sampling method used was a probability sampling technique with proportionate stratified random sampling. The data analysis technique used is multiple linear regression analysis. The sample in this study was 30 LPDs and 90 respondents in LPDs in Tabanan Regency. Respondents in this research were the chairman, treasurer and supervisory body of the LPD in Tabanan Regency. Based on the results of the analysis, it was found that GCG had a negative effect on the tendency of accounting fraud in LPD Tabanan Regency. This means that the better the GCG, the level of tendency for accounting fraud in the Tabanan Regency LPD will decrease. The existence of good organizational governance and continuous evaluation of operational activities helps in minimizing the tendency for accounting fraud. Organizational culture has a negative effect on the tendency of accounting fraud. This means that the better the organizational culture in the Tabanan Regency LPD, the lower the tendency for accounting fraud to occur. Keywords: Good Corporate Governance, Organizational culture, Accounting fraud, LPD